Kualitas Keju yang Dihasilkan dari Susu Kambing Ras Kaligesing pada Bulan Laktasi yang Berbeda (Cheese Quality Made From Milk of Ettawa Crossbred Goat, Based on Different Lactation Stages) - Rizky Yudatama; Tridjoko Wisnu Murti; Yustina Yuni Suranindyah (Buletin Peternakan, 2010)
The objective of the experiment was to evaluate the effect of lactation stages on the quality and flavor of 2 months ripened cheese. The experiment was conducted from December 2009 until April 2010. Five goats were used as samples. Milk were collected at 7 days and 30 days post kidding. Cheeses were coagulated using rennet which produced by extracting dried abomasum of 10 days old goat kid. Fresh cheeses were analyzed for its quality and kept for 2 months. After 2 month, ripened cheeses were analyzed for its quality and flavor. Parameters observed were cheese’s physical quality (cheese yield and tenderness), chemical quality (pH, protein, fat, moisture, ash, calcium) and flavor (for ripened cheeses). Cheese yield, tenderness, pH, protein, fat, moisture, ash, and calcium composition were analyzed using Repeated Measurement of General Linear Model and flavor quality was analyzed using Mann-Whitney Test. The result showed that lactation stages (7 and 30 days post kidding) did not significantly affect cheese yield, pH, protein, fat, and calcium but it had an effect on tenderness, moisture, and ash. Ripening significantly affected flavor such as salty, sour, bitter, and rancidity but not the sweet taste. Ripening was also affected pH and fat composition but moisture, ash, protein, calcium, and tenderness were not affected. It can be concluded that 2 stages of lactation did not significantly affect overall cheese quality, but it was suggested to choose milk from days 30 after partum as cheese raw material since cheeses from days 7 milk have a flavor defect (bitter) and this kind of milk is still needed by the kids ofthe goat.(Key words: Kaligesing race goat’s milk, Cheese quality, Cheese ripening, Cheese flavor, Stage of lactation)